2002
DOI: 10.1002/1099-0690(200204)2002:7<1143::aid-ejoc1143>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

A Wittig Reaction with 2-Furyl Substituents at the Phosphorus Atom: Improved (Z) Selectivity and Isolation of a Stable Oxaphosphetane Intermediate

Abstract: Wittig reactions with ylides bearing one, two or three 2‐furyl groups directly bound to the phosphorus atom have been studied. Greatly improved (Z)‐alkene selectivities of up to 98:2 could be observed if 2‐furyl groups were present. Monitoring of the reactions by NMR spectroscopy revealed only oxaphosphetane intermediates, which became more stable with increasing number of 2‐furyl substituents bound to the phosphorus atom. Oxaphosphetane 10d, with three furyl groups, was successfully isolated, and the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 30 publications
4
34
0
Order By: Relevance
“…We showed that this change of selectivity, which was rather dramatic in many cases, could be easily accommodated within the emerging consensus 4,8,9,10,11,12,13,14,15,16,17,18 on the mechanism of Li-salt free Wittig reactions: [2+2] cycloaddition of ylide and aldehyde to give oxaphosphetane (OPA) followed by cycloreversion to phosphine oxide and alkene (see Scheme 2). Therefore our results also provided strong experimental support for that mechanism.…”
Section: Introductionsupporting
confidence: 71%
“…We showed that this change of selectivity, which was rather dramatic in many cases, could be easily accommodated within the emerging consensus 4,8,9,10,11,12,13,14,15,16,17,18 on the mechanism of Li-salt free Wittig reactions: [2+2] cycloaddition of ylide and aldehyde to give oxaphosphetane (OPA) followed by cycloreversion to phosphine oxide and alkene (see Scheme 2). Therefore our results also provided strong experimental support for that mechanism.…”
Section: Introductionsupporting
confidence: 71%
“…18,19,20 -Reactions showing atypical stereoselectivity, 21,22,23,24,25,26,27 which can be induced e.g. by the use of phosphonium ylides with modified "spectator substituents" on phosphorus, 21,22,24,26 by the use of trialkylgallium base to 10 generate the ylide, 27 and by the addition of methanol at low temperature to the oxaphosphetane adducts from reactions of non-stabilised ylides. 22 -New reaction conditions.…”
Section: Ementioning
confidence: 99%
“…The formation of oxaphosphetane requires rotation around the C-O bond, promoting the erythro configuration of the oxaphosphetane and, consequently, the (Z) olefin. It seems that the oxaphosphetane-forming step is believed to resemble a concerted [2+2] cycloaddition between the ylide and the carbonyl compound, 33 then it can open to zwitterions which are free to rotate to the thermodynamically more stable threo isomers before decomposing to products.…”
Section: Aliphatic Aldehydesmentioning
confidence: 99%